2017
DOI: 10.1007/jhep09(2017)028
|View full text |Cite
|
Sign up to set email alerts
|

A higher-order Skyrme model

Abstract: We propose a higher-order Skyrme model with derivative terms of eighth, tenth and twelfth order. Our construction yields simple and easy-to-interpret higher-order Lagrangians. We first show that a Skyrmion with higher-order terms proposed by Marleau has an instability in the form of a baby-Skyrmion string, while the static energies of our construction are positive definite, implying stability against time-independent perturbations. However, we also find that the Hamiltonians of our construction possess two kin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
0
26
0
1
Order By: Relevance
“…We found that a secondary branch of solutions emerges at α max , extending backwards in α -figure 3 (right panel). Along this second branch, both σ(0) and f 1 decrease as α decreases, while the value of the physical mass 8 An approximate form of the solutions compatible with these conditions can easily be constructed. For example, the small−r expansion contains two essential parameters, F (0) and σ(0).…”
Section: Jhep11(2017)037mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a secondary branch of solutions emerges at α max , extending backwards in α -figure 3 (right panel). Along this second branch, both σ(0) and f 1 decrease as α decreases, while the value of the physical mass 8 An approximate form of the solutions compatible with these conditions can easily be constructed. For example, the small−r expansion contains two essential parameters, F (0) and σ(0).…”
Section: Jhep11(2017)037mentioning
confidence: 99%
“…This condition is also implied by the regularity of energy and angular momentum densities as r → r H . Then the function F (r) possess an approximate solution near the horizon (with λ 2 = 0), which, up to order O(r − r H ) reads: 8) all higher order coefficients being determined by F (r H ) > 0. The profiles of a typical solution on a given MP background are shown in figure 8.…”
Section: Jhep11(2017)037mentioning
confidence: 99%
“…The corresponding vortex equation itself was already introduced in [18] in a different context. Another BPS vortex equation studied in [17] ("Bradlow vortices") may have solutions only if the volume of the manifold is equal to the Bradlow volume, so that the "Bradlow bound" is converted into a "Bradlow equation" (for more on this model see [19]). …”
Section: The Bradlow Bound-abelian-higgs Vorticesmentioning
confidence: 99%
“…The minimal construction of Ref. [28] limits the terms such that there are no powers of a derivative in the i-th direction higher than four. This leaves us with two independent terms, as we will see and the coefficients in Ref.…”
Section: The 2 + 4 + 8 Modelmentioning
confidence: 99%
“…In particular, in Ref. [28] we showed that although the latter construction gives stable radial equations of motion, the angular directions contain instabilities which can be triggered by a baby-Skyrme string in the baryon number 0 sector. For a BH hair configuration it is even worse, as the expansion of the Einstein equation yields a first derivative of the profile function at the horizon which 1 The name may suggest that the model can easily be supersymmetrized, but that is not the case due to the target space being non-Kähler and odd dimensional.…”
mentioning
confidence: 98%